LECTIN RECEPTORS EXHIBITING IN RAT PROGENY SKIN STRUCTURAL COMPONENTS IN PRENATAL AND EARLY POSTNATAL PERIODS ON THE BACKGROUND OF MATERNAL HYPOTHYROIDISM - Yashchenko, A.M.; Strus, Ch.I.; Smolkova, O.V. (World of Medicine and Biology, 2013)
General morphology and lectin receptors cytotopography in rat progeny skin structural components were studied in prenatal and early postnatal periods on the background of maternal experimental hypothyroidism. Slices of skin, taken from the back of progeny of the control and hypothyroid rat females on the 16th day of embryogenesis and on the 1st day of postnatal development, were fixed in 4% neutral formalin, embedded in paraffin. Sections were stained by hematoxylin and eosin, basic brown, PAS reaction was carried out. Glycoconjugates of the skin were studied by the method of lectin peroxidase technique with the use of the set of the following lectins: ConA, PNA, RCA, HPA, WGA, SNA, LABA, and LTFA. Rat skin acquires the definite structure on the 1st day of postnatal development. There is no essential difference in progeny skin of control and hypothyroid rat females on the 16th day of embryonic development. LTFA lectin may be marker of Langerhans cells. Modification of αNАcDGal, αNАcDGlcNАNА, Neu5Ас(α2-6), Gal/NАcGal, DGalß1›3D-GalNAc and αL-Fuc glycoconjugates is observed on the background of maternal experimental hypothyroidism of rat females in progeny skin on the 1st day of postnatal development. To those glycoconjugates belongs the role of adhesive contacts formation, differentiation and proliferation in cells of epidermis, dermis and their derivatives.
Keywords: skin; rat; hypothyroidism; lectins; histochemistry